Diagnostic Uncertainty and Insurance Coverage in Credence Goods Markets - Loukas Balafoutas; Helena Fornwagner; Rudolf Kerschbamer; Matthias Sutter; Maryna Tverdostup (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2020)
Credence goods markets - like for health care or repair services - with their informational asymmetries between sellers and customers are prone to fraudulent behavior of sellers and resulting market inefficiencies. We present the first model that considers both diagnostic uncertainty of sellers and the effects of insurance coverage of consumers in a unified framework. We test the model?s predictions in a laboratory experiment. Both in theory and in the experiment diagnostic uncertainty decreases the rate of efficient service provision and leads to less trade. In theory, insurance also decreases the rate of efficient service provision, but at the same time it also increases the volume of trade, leading to an ambiguous net effect on welfare. In the experiment, the net effect of insurance coverage on efficiency turns out to be positive. We also uncover an important interaction effect: if consumers are insured, experts invest less in diagnostic precision. We discuss policy implications of our results.
Keywords: C91; C72; D82; G22; 330; Credence goods; experiment; diagnostic uncertainty; insurance coverage; welfare